Artikel Review Fitokimia : Efektivitas Refluks Sebagai Metode Ekstraksi - Isafani, Nungki Hatit; Nailah Mutiara Wahid; Marscha Dwi Lestari; Ryan Satria Pranata; Meiva Shafa Herdini; M. Ilham Fannany; Helmalia Jelita Putri; Anisa Rachman; Nadya Tazkiyah Tsabitah; A’Yunil Hisbiyah; Ivan Charles S.Klau; Arista Wahyu Ningsih (CV. ITTC INDONESIA, 2025)
The reflux extraction method is a technique that uses a solvent at its boiling point for a certain time with a stable solvent volume, due to the presence of a reflux condenser. This method is generally used to extract coarse-textured and heat-resistant materials, because the process involves continuous heating. The main advantage of the reflux method is its ability to efficiently extract samples with coarse textures. This article discusses the effectiveness of reflux extraction by outlining its working principle, factors that influence extraction results, its advantages and disadvantages, applications to various phytochemical compounds, and also innovative developments of this method. In the reflux method, the solvent is heated to its boiling point and the solvent vapor formed is recondensed so that it can circulate repeatedly. This process allows for more efficient and stable extraction. Several factors that influence extraction results include the type of solvent, temperature, stirring speed, solvent, the ratio between the material and the surface area of ​​the material, and the length of the extraction time. Sari's research results showed that the galactomannan yield from coconut pulp using aquadest solvent reached 3.82%, higher than Zultiniar's research using methanol with a yield of 0.90%. This result is consistent with the research of Zulmi et al. who extracted galactomannan from palm fruit using aquadest solvent, while Tarigan who used ethanol obtained a lower yield.